1996
DOI: 10.1097/00007890-199609150-00022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Assessment of Mycophenolic Acidinduced Immunosuppression in Renal Transplant Recipients

Abstract: The combination of pharmacokinetic and pharmacodynamic monitoring of immunosuppressive drugs provides a novel method for the optimization of drug dosing. We chose to investigate this with the use of mycophenolic acid (MPA), an immunosuppressive drug that mediates its effect by the inhibition of inosine monophosphate dehydrogenase (IMPDH), a key enzyme in the de novo biosynthesis of purines. The relationship between MPA concentration in plasma, IMPDH activity in whole blood, and nucleotide concentration in lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(78 citation statements)
references
References 22 publications
8
68
0
2
Order By: Relevance
“…In both populations, IMPDH activity inhibition persisted for 4 h, returning to baseline after 11 h and before the next dose (25)(26)(27). Langman et al also found that significant inhibition of IMPDH activity persisted for at least 8 h despite low MPA levels (28). More recently, Vethe et al demonstrated that in kidney allograft recipients, the maximal inhibition of IMPDH activity occurs 1 h after MMF intake (29).…”
Section: Discussionmentioning
confidence: 96%
“…In both populations, IMPDH activity inhibition persisted for 4 h, returning to baseline after 11 h and before the next dose (25)(26)(27). Langman et al also found that significant inhibition of IMPDH activity persisted for at least 8 h despite low MPA levels (28). More recently, Vethe et al demonstrated that in kidney allograft recipients, the maximal inhibition of IMPDH activity occurs 1 h after MMF intake (29).…”
Section: Discussionmentioning
confidence: 96%
“…The concentration-dependence of increased surface expression of adhesion molecules by MPA was similar for both VCAM-1 and E-selectin: an increase was detectable at 0.5 mM, the half-maximal e ective concentration of MPA, which increases the expression of the cell adhesion molecules VCAM-1 and E-selectin on TNFa-activated EC, was estimated to &1 mM, and a plateau was reached at 10 mM (Figure 4). ICAM-1 surface expression remained unchanged, but marked increases of VCAM-1 and E-selectin surface expression were observed at the clinically relevant concentrations of 0.5 ± 10 mM (Langman et al, 1996).…”
Section: Increased Adhesion Of U937 Cells To Tnfa-treated Human Ec Bymentioning
confidence: 90%
“…(68). In addition, others report, that IMPDH-activity on peak concentration of MPA is approximately 40% and could be suppressed for 8 hours (69). In general, it is assumed, that IMPDH activity has a substantial interindividual, but low intraindividual variability (70).…”
Section: Inhibition Of Impdh-activitymentioning
confidence: 99%